Clawed and dangerous - Brown, Rita Mae; Brown, Sneaky Pie, 1982- (Brown, Rita Mae. Mrs. Murphy mystery., 2026)
"Death stalks the Blue Ridge Mountains once again and Mary Minor "Harry" Harristeen, along with her beloved cats, is on the case."--Provided by publisher.